Non-Usual Nominations of Person in Forum Discourse - E. V. Shchenikova (Научный диалог, 2017)
Non-usual nouns are considered - names of persons and groups that are created and used in the speech of users of a number of thematic Internet forums, specifically car forums, forums for cat lovers and dog lovers. These units are part of a dynamic verbal system, which, on the one hand, is able to reflect the latest trends in language development because of the weak normalizing, and on the other hand, potentially is able to have an impact on contemporary speech practices that determines the relevance of the study because of the wide coverage of users. The groups of considered derivatives are briefly presented in terms of their derivational structure. The typology of ways of word formation typical for the surveyed segment of forum discourse are suggested. Their most significant varieties and manifestations are noted. The focus is on “pure” (I. S. Ulukhanov) ways of word formation. Typical derivational formants are distinguished and characterized in the semantic and stylistic aspect. The thematic specificity of the derivatives formed in certain ways is identified. Attention is paid to structural, semantic and stylistic deviations from norms and rules that are acceptable in the formation of new words. The ambiguous approach to the consideration and interpretation of some items in the literature is noted.